Measurement and Simulation of Demagnetization in a Prototype Halbach Array Quadrupole - Alexander Bainbridge; Alexander Hinton; Clive Hill; Thomas Smith; Ben Pine; Neil Thompson (Metrology)
We present the design, construction, measurement, and troubleshooting of a prototype hybrid Halbach quadrupole magnet. This magnet was significantly under-strength due to local demagnetization in the permanent magnet material. We discuss how this effect was uncovered, how it was verified by performing Hall probe measurements of the individual magnet blocks, and how the effect was reconstructed in simulations.